INOVASI KREATIF BERBASIS DAUR ULANG: PENGABDIAN MASYARAKAT DI BRSBKL DINSOS MELALUI PEMBUATAN KALENDER ASA - Isnatasari, Arum; Nuriyatul Azizah, Maula; Hanifah, Auliya (LPPM Universitas Al Muslim, 2025)
Creativity has an important role in helping social rehabilitation for fostered community of the Bina Karya and Laras Social Rehabilitation Center (BRSBKL). The